If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (3x + -4) = (2x + -3) Reorder the terms: 2x + (-4 + 3x) = (2x + -3) Remove parenthesis around (-4 + 3x) 2x + -4 + 3x = (2x + -3) Reorder the terms: -4 + 2x + 3x = (2x + -3) Combine like terms: 2x + 3x = 5x -4 + 5x = (2x + -3) Reorder the terms: -4 + 5x = (-3 + 2x) Remove parenthesis around (-3 + 2x) -4 + 5x = -3 + 2x Solving -4 + 5x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 5x + -2x = -3 + 2x + -2x Combine like terms: 5x + -2x = 3x -4 + 3x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 3x = -3 + 0 -4 + 3x = -3 Add '4' to each side of the equation. -4 + 4 + 3x = -3 + 4 Combine like terms: -4 + 4 = 0 0 + 3x = -3 + 4 3x = -3 + 4 Combine like terms: -3 + 4 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| 1+(1)(1)= | | (1)(1)+1= | | 9x-7=-3x+29 | | -1.4121-(1-2.4)= | | 4+(2)(3)= | | 4(2+3)= | | 7x-14=-3x+6 | | 3(x-1)(x+1)=9 | | 7+(1)(-2)= | | 7(1)+(-2)= | | 7(1+-2)= | | 3(2x-1)=4(x+2) | | 7(7x-2)=49x-14 | | -5+2(4)= | | -5(2)+4= | | y-4=-2/3x | | -5(1-2n)=15 | | -5(2+4)= | | 9x+7=-5+7x+16 | | -3(t+3)=15 | | 47-15=4(x-6) | | 70+5y-32=17y-11-5y | | 2+(-3)(4)= | | (36m-9mn=45n)/9 | | k^2+2k+-60=0 | | -4(p+5)= | | 4(2x+9)=-7x-24 | | 2(-3+4)= | | 50+3x= | | 5=-5a+2a | | 4(k+0.5)=2k+k+6 | | 1000x+2500=-4000 |